PENGARUH DIFERENSIASI PRODUK KRIPIK TEMPE TERHADAP LOYALITAS KONSUMEN - Rina Rifqie Mariana (Universitas Pendidikan Indonesia (UPI), 2009)
All producers offer the superiority of their products by showing the unique thing among the differences called differentiation. This strategy is used to keep the product position not to decline in its Life Cycle. All these are to keep the consumers’ loyalty. This research used correlation aiming to know the influence of product’s (X) differentiation consisting of: package (X1), Price (X2), Service (X3), Brand (X4) and quality (X5) on consumers’ loyalty (Y) through consumers’ satisfaction (Z) partially and simultaneously. The samples are 100 respondents. The technique of data collection is closed questionnaire. The data analysis used is double linear regression analysis using t test and F, and PATH analysis to measure the influence of X variable on Y through Z. The result showed (1) There is a significant influence of package, price, service, and quality product but brand. Brand doesn’t influence consumers’ loyalty. (2) There is a significant influence of consumers’ satisfaction on loyalty (3) There is a significant influence of package, price, service, and quality on loyalty through satisfaction. However, brand doesn’t give a significant influence on loyalty through satisfaction. The result showed that the most influencing point on loyalty is the package and product quality.. It is suggested to (1) Kripik tempe producers to improve their work on service speed, quality of product and kinds of flavor, package cleanliness, and package specification. (2) Next researchers to add the research object and area.